Relative Risk Aversion: A Meta-Analysis - Ali Elminejad; Tomas Havranek; Zuzana Irsova (ZBW - Leibniz Information Centre for Economics, 2022)
We collect 1,021 estimates from 92 studies that use the consumption Euler equation to measure relative risk aversion and that disentangle it from intertemporal substitution. We show that calibrations of risk aversion are typically larger than estimates thereof. Moreover, reported estimates are typically larger than the underlying risk aversion because of publication bias. After correction for the bias, the literature suggests a mean risk aversion of 1 in economics and 2–7 in finance contexts. The reported estimates are systematically driven by the characteristics of data (frequency, dimension, country, stockholding) and utility (functional form, treatment of durables). To obtain these results we use nonlinear techniques to correct for publication bias and Bayesian model averaging techniques to account for model uncertainty.
Keywords: C83; D81; D90; 330; Euler equation; risk aversion; Epstein-Zin preferences; meta-analysis; publication bias; Bayesian model averaging